ChemInform Abstract: Diastereoselective [2 + 2] Photocycloaddition of Cyclohexenone Derivative with Olefins in Supercritical Carbon Dioxide. Issue 44 (14th October 2013) - Nishiyama, Yasuhiro; Nakatani, Kazuya; Tanimoto, Hiroki; Morimoto, Tsumoru; Kakiuchi, Kiyomi
Abstract An enhancement of conversion is observed for the title reaction around the critical density of CO2 due to a clustering effect.